Digital games for international development: A field theory perspective. (October 2019) - Fisher, Jolene
While serious games have been used within the field of international development since 2005, their adoption as tools for social and behavior change has remained fairly limited. Using Bourdieu's theory of practice as an analytical framework, this study examines the tensions created when the fields of international development and serious games are brought together. In-depth interviews with development practitioners and game experts responsible for creating the nonprofit Half the Sky Movement's mobile phone and Facebook games are used to examine how logistical considerations and ideological conflicts between agents from differing fields shape the limitations and possibilities of bringing games into the development space. Further, this study analyzes the new forms of Bourdieu's concepts of habitus and capital created through this overlap in fields, filling an existing gap in the extant literature on the production and use of games for international development.